Orthodontıc Approach In Tmj Ankylosıs Case After Late Perıod Surgıcal Operatıon - Sema Yüksel; Tuba Tortop Üçem (Galenos Yayinevi, 1995)
After surgical operation of a bilateral TMJ ankylosis cases at age 21, a spring loaded bite block was applied to increase mandibular functions. At the end of the one year maximum bite opening was increased, openbite was decreased and molar relationship was corrected.